EFEKTIVITAS WORKSHOP “ACADEMIC WRITING” DALAM MENINGKATKAN RESILIENSI AKADEMIK MAHASISWA SEMESTER AKHIR - Ika Apriati Widya Puteri (Proyeksi: Jurnal Psikologi, 2022)
Academic resilience is an individual's response to affective, cognitive, and behavioral in the face of academic difficulties or failures that he experienced. One of the efforts that can be done so that students have academic resilience is to provide preparation for thesis work. When students already have knowledge of thesis writing techniques, students can feel more prepared, so that they will grow a feeling of optimism in working on their thesis and confidence that they will be able to complete the thesis on time. The “Academic Writing” workshop is a series of workshops to provide knowledge and training to students regarding thesis writing. The themes that will be discussed in this workshop are how to make titles and raise research problems, thesis writing techniques, using reference manager applications, and various research methods. The purpose of this study was to determine the effectiveness of the "Academic Writing" workshop in improving the academic resilience of final semester students. This research method is a pre-experimental design with the one-group pretest-posttest design. Measurements were made with The Academic Resilience Scale (ARS-30) which was carried out 2 times, namely before the intervention and after the intervention. The results of the study using a paired sample t-test showed that the "Academic Writing" workshop did not significantly increase the academic resilience of final semester students (t = 0.811, p = 0.430).